Cortical microstructural abnormalities in dementia with Lewy bodies and their associations with Alzheimer’s disease copathologies - Elijah Mak; Robert I. Reid; Scott A. Przybelski; Angela J. Fought; Timothy G. Lesnick; Christopher G. Schwarz; Matthew L. Senjem; Sheelakumari Raghavan; Prashanthi Vemuri; Clifford R. Jack; Hoon Ki Min; Manoj K. Jain; et al. (npj Parkinson's Disease)
Abstract Dementia with Lewy bodies (DLB) frequently coexists with Alzheimer’s disease pathology, yet the pattern of cortical microstructural injury and its relationship with amyloid, tau, and cerebrovascular pathologies remains unclear. We applied neurite orientation dispersion and density imaging (NODDI) to assess cortical microstructural integrity in 57 individuals within the DLB spectrum and 57 age- and sex-matched cognitively unimpaired controls by quantifying mean diffusivity (MD), tissue-weighted neurite density index (tNDI), orientation dispersion index (ODI), and free water fraction (FWF). Amyloid and tau levels were measured using PiB and Flortaucipir PET imaging. Compared to controls, DLB exhibited increased MD and FWF, reduced tNDI across multiple regions, and focal ODI reductions in the occipital cortex. Structural equation modeling revealed that APOE genotype influenced amyloid levels, which elevated tau, leading to microstructural injury. These findings highlight the role of AD pathology in DLB neurodegeneration, advocating for multi-target therapeutic approaches addressing both AD and DLB-specific pathologies.